2019
DOI: 10.5539/jas.v11n5p419
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Rhizomes and Starch Quantification in Cultures of Different Vegetative Propagules of Arrowroot

Abstract: Arrowroot rhizomes are rich in carbohydrate and are commonly grown by family farmers who have an important source of income in this activity and play a prominent role in the conservation of the species. There are few studies on the phytotechnical aspects of culture. The objective of this work was to evaluate the productive capacity of the ‘common’ arrowroot using different sizes and forms of propagation, aiming at the production of rhizomes and arrowroot starch, in different agricultural cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The possible causes for the difference in starch content in the three species of tubers were the genetic factor of the tuber species and the size of the rhizome seeds [49]. The research on rice also showed that different varieties of rice produced varied starch content [50].…”
Section: Land Equivalent Ratiomentioning
confidence: 99%
“…The possible causes for the difference in starch content in the three species of tubers were the genetic factor of the tuber species and the size of the rhizome seeds [49]. The research on rice also showed that different varieties of rice produced varied starch content [50].…”
Section: Land Equivalent Ratiomentioning
confidence: 99%
“…The cultivar Seta was faster and more productive in terms of dry mass accumulation in rhizomes, than 'Comum'. The starch content in arrowroot rhizomes can vary with the cultivar, 'Seta' had 11.32% (SOUZA et al, 2019a) and that for 'Comum' was 20.28% (SOUZA et al, 2019b) and the crop cycle (18 -23%) (FERRARI; LEONEL; SARMENTO, 2005;AMANTE et al, 2020). Thus, it is expected that 'Comum' arrowroot plants (156.76 g plant -1 ) can produce a far higher amount of starch than 'Seta' (92.71 g plant -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the advantage of arrowroot starch is its high nutritional value and absence of gluten making it an excellent raw material for producing dietary supplements for patients suffering from Celiac disease (GUILHERME et al, 2019). The starch content in arrowroot rhizomes can vary with the crop cycle (FERRARI; LEONEL; SARMENTO, 2005;AMANTE et al, 2020) and with the cultivar (SOUZA et al, 2019a;SOUZA et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The price of the arrowroot starch in the national market has reaches values of R$ 15.00 to 39.00 per kg, because of this, the cultivation of arrowroot has become a potential option in Brazilian agribusiness, especially for family Rev. Ceres, Viçosa, v. 66, n.5, p. 323-332, sep/oct, 2019 agriculture (Moreno et al, 2017;Santos, 2019;Souza et al 2019;Vieira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%